Development of organic–inorganic hybrid beads from sepiolite and cellulose for effective adsorption of malachite green. Issue 62 (9th August 2017) - Jiang, Xin; Wang, Sidun; Ge, Lan; Lin, Fengcai; Lu, Qilin; Wang, Ting; Huang, Biao; Lu, Beili
Abstract : A facile approach has been developed to fabricate well defined organic–inorganic hybrid beads from widely available bamboo pulp and sepiolite, in expectation of an alternative green adsorbent for the removal of organic dyes. Abstract : Organic–inorganic hybrid adsorbents based on sepiolite and cellulose were prepared through an easy-to-handle procedure. Hydrogen-bonding existed between the silanol groups (Si–OH) on the sepiolite surface and the hydroxyl groups of the cellulose structure resulting in the formation of hybrid beads with good synergistic effects. Incorporation of the inorganic molecule sepiolite into the renewable polymer cellulose opened an opportunity for the development of alternative environment-friendly adsorbents with improved adsorption efficiency as well as enhanced thermal stability compared with neat cellulose beads. The utility of the obtained sepiolite/cellulose beads was demonstrated by investigating their performance for the removal of malachite green (MG). The maximum adsorption capacity of MG on sepiolite/cellulose beads was close to the calculated results from the Langmuir adsorption isotherm, and the adsorption kinetics followed well to the pseudo-second-order model.